Pemberdayaan Disabilitas Mental Melalui Program Karepe Dimesemi Bojo Di Kabupaten Jombang - Tukiman; Temi Puji Lestari; Esti Puji Rahayu; Rohmatul Afrida Nor Laili (Jurnal Syntax Transformation, 2021)
In Jombang Regency, there are still many people with mental disabilities that need attention. If persons with mental disabilities are not considered, it will cause public problems in the form of social problems and cause unrest in the community. However, the Jombang District Government has issued regulations governing the welfare of disabilities. Efforts that can be made to improve the welfare of persons with disabilities are through empowerment. One of the mental disabilities empowerment efforts carried out in Jombang Regency is the creation of a mental disability program called the KAREPE DIMESEMI BOJO Program (Rehabilitation Area for Persons with Mental Prosperous Disabilities Mandiri, Jombang Regency). This study aims to determine the implementation of empowerment with mental disabilities through KAREPE DIMESEMI BOJO in Bongkot Village, Peterongan District, Jombang Regency. This research uses descriptive qualitative research methods with data collection techniques through observation, interviews, and documentation. The theoretical concept used is the concept of Purwanto and Sulistyastuti's Implementation Theory (2015: 86). The results of this study indicate six factors that determine the success or failure of an implementation process which is an indicator that has been fulfilled in the implementation of empowerment of mental disabilities through KAREPE DIMESEMI BOJO in Bongkot Village, Peterongan District, Jombang Regency. So in conclusion, the implementation of mental disability empowerment through KAREPE DIMESEMI BOJO in Bongkot Village, Peterongan District, Jombang Regency has been going well.